The correlation between blood alcohol concentration and biological fl uids in corpeses of unnatural death - Narongchai, Paitoon; Narongchai, Siripun (Biomedical Sciences and Clinical Medicine, 2024)
Objective To compare the alcohol concentration in blood with that in biological fluids in order to use the latter for evidence in the forensic process of equity when blood cannot be collected from corpses. Material and method Femoral blood, heart blood, urine, vitreous humor and synovial fl uid were collected from 53 corpses of people who died unnaturally and were associated with alcohol consumption. An autopsy and analysis of alcohol were carried our by GC-Headspace at the Forensic Department, Faculty of Medicine, Chiang Mai University. All corpses had been dead from within 2 hours after alcohol consumption, without treatment, decomposition or drowning. Mean and standard deviation were applied for analysis. Result Fifty three corpses were included in this study, according to the set criteria. The ratio of males to females was 12:1 (92%:8%) and the average age 28 years old (range from 18 to 62 years old). The mean number of samples(bracketed below) in heart blood alcohol concentration (HAC), femoral blood alcohol concentration (FAC), vitreous humor alcohol concentration (VAC), urine alcohol concentration (UAC) and synovial fluid alcohol concentration (SAC) was 194 (46), 194 (53), 219 (49), 203 (50) and 201 (34) mg%, respectively, and the highest alcohol concentration in each specimen type was 556, 529, 511, 493 and 364 mg%, respectively. The ratio of alcohol concentration between heart blood, vitreous humor, urine, synovial fluids to femoral blood was 0.99, 1.14, 1.04 and 1.04 to 1.00, respectively. Conclusion The alcohol concentration in biological fluids was related closely with that in blood from the corpses of people that died at the death scene or within 2 hours after alcohol consumption, without treatment, decomposition or drowning.